1987
DOI: 10.4315/0362-028x-50.5.418
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profile of Cumin Seeds and Chili Powder Sold in Retail Shops in the City of Bombay

Abstract: A detailed evaluation of the microbial profile of 2 spices, viz. cumin seeds and chili powder, sold in retail shops in the city of Bombay, revealed high aerobic plate counts ranging from 2 × 106/g - 2 × 108/g for chili powder and 1.0 × 104/g to 1.0 × 108/g for cumin. Among the bacteria present, 50–95% constituted sporeformers, which included amylolytic and proteolytic bacilli in both the spices. Aspergillus group was predominant among fungi in chili powder samples. No fungi were found in cumin seed samples exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
4
10
1
1
Order By: Relevance
“…The preparations found to be within an unacceptable range (TAMB >6 log CFU/g) included: cumin, ginger, pimento, turmeric, parsley, with the maximum mean load of the fennel preparation of 7.36 log CFU/g. These preparations were also reported to contain high incidences of contamination in a number of studies carried out by other researchers (Abou Donia, 2008;Banerjee & Sarkar, 2003;Baxter & Holzapfel, 1982;Bhat et al, 1987;De Boer, Spiegelenberg, & Janssen, 1985;Garcia et al, 2001;. In the present study, 40% of spices (12 of 30) were of marginal quality (TAMB within 4e6 log CFU/g), and another 40% (12 of 30) were acceptable (TAMB <4 log CFU/g).…”
Section: Microbiological Quality Of Spicessupporting
confidence: 46%
See 2 more Smart Citations
“…The preparations found to be within an unacceptable range (TAMB >6 log CFU/g) included: cumin, ginger, pimento, turmeric, parsley, with the maximum mean load of the fennel preparation of 7.36 log CFU/g. These preparations were also reported to contain high incidences of contamination in a number of studies carried out by other researchers (Abou Donia, 2008;Banerjee & Sarkar, 2003;Baxter & Holzapfel, 1982;Bhat et al, 1987;De Boer, Spiegelenberg, & Janssen, 1985;Garcia et al, 2001;. In the present study, 40% of spices (12 of 30) were of marginal quality (TAMB within 4e6 log CFU/g), and another 40% (12 of 30) were acceptable (TAMB <4 log CFU/g).…”
Section: Microbiological Quality Of Spicessupporting
confidence: 46%
“…In surveys in India, yeasts were also detected in cumin, at levels ranging between w1 and 4 log CFU/g (Banerjee & Sarkar, 2003;Bhat et al, 1987). Molds were present in 50% (15 of 30) of spices at levels 1.01 log CFU/g e 3.64 log CFU/g with the highest count in onion (Table 1).…”
Section: Microbiological Quality Of Spicesmentioning
confidence: 92%
See 1 more Smart Citation
“…B. cereus ranked as one of the most common cause of food poisoning in some countries (Konuma et al, 1988;Todd, 1996). In some studies, investigators were found B. cereus in spices and herbs in different levels (Bhat et al, 1987;Deambrosis and Da Silva, 1992;Kenifel and Berger, 1994;Konuma et al, 1988;Powers et al, 1976;Rosenberger and Weber, 1993). In our study, the highest contamination levels were obtained from chopped red pepper, powdered black paper, cumin powder and chopped mint samples.…”
Section: Resultsmentioning
confidence: 99%
“…of B. cereus. According to Bhat et al (1987), the isolation rate of B. cereus was high in chilli powder. In the cumin seed samples, however, B. cereus incidence was lower than chilli powder samples.…”
Section: Resultsmentioning
confidence: 99%